for all n>=3 prove that 2^{n+1} does not divide 3^{^2^(n-2)} - 1 i have figured out by crunching numbers that 2^{n} divides 3^{^2^(n-2)} - 1 but having trouble trying to start a proof. any help appreciated.
Follow Math Help Forum on Facebook and Google+
help with proof for number theory, possibly using induction?
so prove it does not work for n=3, then show it does not work for n=4? i feel as though there should be a more solid proof than that.
It's a general inductive proof. You show for n=3, assume for n-1, and show it holds for n.
View Tag Cloud